English System Justification in the Social Explanation of the Violence against Minoritized Groups - Santos Mateus, Karla; Pereira, Cicero Roberto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Violence against minoritized groups continues to be pervasive despite social norms prescribing nonviolence because it is legitimized in democratic societies. It is likely that, when individuals are faced with the occurrence of violence within their social environment, they justify it because the individuals tend to perceive and defend all social events as just, legitimate, and necessary. We addressed this possibility in two experimental studies in which we manipulated the minoritized group victim of violence (black vs. women vs. gays vs. control). In Study 1 (N= 104), participants blamed more women for their own victimization; blamed the perpetrator less when the victim was black people and depicted homophobic violence as a social issue similar to general violence in society. Study 2 (N = 217) went further by showing that these effects occur especially when participants were asked to respond as thought by society. We discuss explanations for violence as examples of individuals’ tendency to justify the social system and provide new insights for the secondary victimization research.